Superhard high-entropy diboride coating with nano-composite structure as well as preparation method and application of superhard high-entropy diboride coating
By using nanocomposite structure ultra-hard high entropy diboride coating technology in boride coating, combined with magnetron sputtering technology of HfMoNbZr target and TiB2 target, the problem of insufficient hardness and toughness of existing boride coatings is solved. , a nanocomposite structural coating with high hardness and high toughness is achieved, significantly improving the wear resistance of the coating.
Patent Information
- Application Number
- CN202411512244.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing boronide coatings have shortcomings in hardness and toughness, resulting in brittle cracking and poor wear resistance, limiting their application in the coating industry.
Using nanocomposite structure ultra-hard high entropy diboride coating, the high-power pulse magnetron sputtering and DC magnetron sputtering combined with co-sputtering technology is used to form a high hardness and high toughness (TiHfMoNbZr) with high hardness and high toughness (TiHfMoNbZr) ) Nanocomposite structure of B2 solid solution and TiHfMoNbZrB alloy.
It achieves high hardness (34~42GPa) and high toughness of the coating, significantly improves fracture toughness and wear resistance, and is suitable for wear-resistant surface protective coatings.
Smart Images

Figure CN119392165A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of superhard wear-resistant surface protective coatings, and particularly relates to a nano-composite structure superhard high-entropy diboride coating and a preparation method and application thereof. Background Art
[0002] Borides are chemically inert, chemically stable, and conductive, and have high hardness and melting points. They are widely used in microelectronic components, solar power generation, cutting tools, and extreme environments such as aerospace and nuclear industries. TiB2, a transition metal boride, has rich and excellent multifunctional properties and is a particularly promising ceramic material. It has been widely studied in recent years and is considered to be a potential protective and functional coating material in the future. However, due to the large residual stress, poor oxidation resistance, and low fracture toughness of sputtered TiB2 coatings, the application of TiB2 in the coating industry is greatly limited. Therefore, it is necessary to improve the toughness of boride coatings without significantly sacrificing their hardness to avoid brittle cracking. Summary of the invention
[0003] In order to solve the problem of insufficient hardness or toughness of existing boride coatings, the present invention provides a nano-composite structured ultra-hard high-entropy diboride coating, which has both high hardness and high toughness, can greatly improve the fracture toughness and wear resistance of the boride coating, and has broad application prospects in the field of surface wear-resistant protective coatings.
[0004] The present invention also provides a preparation method and application of a nano-composite structure superhard high-entropy diboride coating.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a nanocomposite structure superhard high entropy diboride coating, and the chemical composition of the coating is as follows in atomic percentage:
[0007] Hf: 2-5%; Mo: 2-5%; Nb: 2-5%; Zr: 2-5%; Ti: 20-24%; B: 63-68%, the remainder being unavoidable impurity elements;
[0008] The microstructure of the coating includes a crystalline phase and an amorphous phase, wherein the crystalline phase is a (TiHfMoNbZr)B2 solid solution of a hexagonal aluminum diboride (hcp) structure with a grain size of 2 to 5 nm;
[0009] The amorphous phase is TiHfMoNbZrB alloy.
[0010] Furthermore, the hardness of the coating is 34-42 GPa, the elastic modulus is 340-378 GPa, and the wear rate is 5.5×10-16 ~1.3×10 -15 m 3 ·N -1 ·m -1 .
[0011] Furthermore, the fracture morphology of the coating shows a dense structure, and the thickness of the coating is 1.7 to 2.2 μm;
[0012] The molar ratio of Hf, Mo, Nb and Zr elements in the coating is about 1:1:1:1.
[0013] Optionally, the coating is prepared by co-deposition of a HfMoNbZr target by high-power pulsed magnetron sputtering and a TiB2 target by DC magnetron sputtering;
[0014] Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the HfMoNbZr target is 1:1:1:1.
[0015] Preferably, the purity of the HfMoNbZr target is >99.99%, and the purity of the TiB2 target is >99.98.
[0016] Based on the same inventive concept, the present invention provides a method for preparing a nanocomposite structured ultrahard high entropy diboride coating, the preparation method comprising:
[0017] The substrate is placed in a vacuum coating device, and a HfMoNbZr target and a TiB2 target are used as target materials, wherein the HfMoNbZr target is connected to a high-power pulsed magnetron power supply, and the TiB2 target is connected to a direct current power supply;
[0018] In a vacuum environment, an inert gas is continuously introduced into the vacuum coating device, and power supplies of the HfMoNbZr target and the TiB2 target are simultaneously turned on to deposit a nano-composite structured ultra-hard high-entropy diboride coating on the surface of the substrate;
[0019] Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the HfMoNbZr target is 1:1:1:1.
[0020] Furthermore, the magnetron sputtering power of the HfMoNbZr target is 80-220 W, the pulse width is 20 μs, the pulse frequency is 1000 Hz, the magnetron sputtering power of the TiB2 target is 240-260 W, the deposition temperature is 400-600° C., the deposition time is 180 min, the substrate bias is a floating potential, and the rotation speed is 15±2 r / min.
[0021] Furthermore, the distances between the HfMoNbZr target and the TiB2 target and the substrate are 8 to 11 cm, and the background vacuum of the vacuum coating equipment is less than 2×10 -3Pa;
[0022] The flow rate of the inert gas is 38-42 sccm.
[0023] Furthermore, the substrate is pre-surface treated to remove impurities on the surface of the substrate.
[0024] Preferably, the substrate comprises a silicon wafer or a 316L stainless steel wafer, the thickness of the silicon wafer is 489-510 μm, the thickness of the 316L stainless steel wafer is 2.9-3.2 mm, and the silicon wafer is of P type and
[100] crystal orientation.
[0025] Based on the same inventive concept, the present invention provides a method for preparing a nano-composite structured ultra-hard high-entropy diboride coating and its application in preparing a wear-resistant protective coating on the surface of a machined part.
[0026] Based on the same inventive concept, the present invention also provides a method for preparing a nano-composite structured ultra-hard high-entropy diboride coating and its application in preparing a tool coating.
[0027] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0028] 1. The present invention discloses a nano-composite structured superhard high entropy diboride coating, which is obtained by co-deposition of HfMoNbZr target with an atomic ratio of equal molar ratio by high-power pulsed magnetron sputtering and TiB2 target by DC magnetron sputtering. The coating has a nano-composite structure, and the crystalline phase is a (TiHfMoNbZr)B2 solid solution with a hexagonal aluminum diboride (hcp) structure, with a grain size of 2 to 5 nm, and the main component of the amorphous phase is TiHfMoNbZrB alloy. The nano-composite structured superhard high entropy diboride coating of the present invention not only has a hardness of up to 42 GPa, but also has high toughness and a wear rate as low as 5.538×10 -16 m 3 ·N -1 ·m -1 It has both high hardness and high toughness, which greatly improves the fracture toughness and wear resistance of the coating, and has broad application prospects in the field of wear-resistant surface protective coating technology.
[0029] 2. The present invention discloses a method for preparing a nano-composite structured superhard high entropy diboride coating. The method uses an HfMoNbZr target and a TiB2 target with an equimolar atomic ratio as target materials for coating deposition, uses high-power pulsed magnetron sputtering and DC magnetron sputtering combined with co-sputtering, has a simple process, and can effectively regulate the element content and structure of the coating. The method adds HfMoNbZr to the TiB2 lattice to form high entropy (TiHfMoNbZr) B2 grains. In addition, the addition of HfMoNbZr inhibits grain growth and refines grains. (TiH The HfMoNbZr)B2 grain size is 2 to 5nm, and the HfMoNbZr that does not enter the TiB2 lattice will exist in the coating in an amorphous form, thus forming a nano-composite structure. This nano-composite structure of (TiHfMoNbZr)B2 grains + amorphous TiHfMoNbZrB alloy simultaneously improves the hardness and toughness of the coating, thereby greatly improving the wear resistance of the coating. The deposited nano-composite high-entropy diboride coating has a dense structure and excellent mechanical properties, which provides ideas for the preparation of future superhard coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 XRD patterns of high entropy diboride coatings prepared in Examples and Comparative Examples of the present invention.
[0032] Figure 2 This is a cross-sectional morphology of the high entropy diboride coating prepared in Example 2 of the present invention.
[0033] Figure 3 The hardness and elastic modulus of the high entropy diboride coatings of the embodiments of the present invention and the comparative examples.
[0034] Figure 4 This is a high-resolution TEM image of the high-entropy diboride coating prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0036] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0038] The overall idea of the present invention is as follows:
[0039] At present, in order to meet the two contradictory requirements of high hardness and high toughness of the coating, multi-component composite coatings can be developed by doping with other borides and refractory ceramics or selecting appropriate elements, and the comprehensive performance of the coating can be improved by designing the composition and microstructure. For example, the TiB2 / Cr nanocomposite coating with the authorization announcement number CN113174571 B has a hardness of 32GPa, which improves the bonding strength and hardness while achieving toughness. For example, the Ti(Si)B2 coating with the authorization announcement number CN112323031 B, which is co-sputtered and deposited by TiB2 target and Si target, has high hardness, corrosion resistance and bottom resistivity, and its hardness is 31GPa. Although the coatings prepared by these two methods have high hardness, they have not reached the superhard level, and there is still a lot of room for improvement.
[0040] Based on this, the present invention proposes a nano-composite structure superhard high-entropy diboride coating and a preparation method thereof. The method adopts HfMoNbZr target with an atomic ratio of equimolar ratio to co-deposit diboride ceramic coating by high-power pulsed magnetron sputtering and TiB2 target by DC magnetron sputtering. The prepared high-entropy diboride ceramic coating has a nano-composite structure, and the crystalline phase is a hexagonal aluminum diboride (hcp) structure of (TiHfMoNbZr)B2 solid solution with a grain size of 2 to 5nm. The main component of the amorphous phase is TiHfMoNbZrB alloy. The coating hardness is as high as 42GPa, reaching the superhard level. At the same time, it also has high toughness, combining high hardness and high toughness, which greatly improves the fracture toughness and wear resistance of the coating.
[0041] Hardness and toughness are important factors affecting the wear rate of coatings. The general method of increasing hardness often sacrifices its toughness, which results in that its wear resistance may not necessarily be improved. In the present invention, the reason for the increase in the hardness of the coating is that the crystalline high entropy (TiHfMoNbZr) B2 grains will cause lattice distortion due to the difference in atomic radius; in addition, the coating has a nanocomposite structure, in which the softer amorphous phase can play a role in strengthening the grain boundaries. In addition, the presence of the softer amorphous phase TiHfMoNbZrB alloy can improve the toughness of the coating. The present invention simultaneously improves the hardness and toughness of the coating, thereby greatly improving the wear resistance of the coating, and has broad application prospects in the field of wear-resistant protective coatings on the surfaces of machined parts, such as protective layers on the surfaces of cutting tools.
[0042] Specifically, the present invention provides a nanocomposite structured ultra-hard high entropy diboride coating, wherein the chemical composition of the coating is as follows in terms of atomic percentage:
[0043] Hf: 2-5%; Mo: 2-5%; Nb: 2-5%; Zr: 2-5%; Ti: 20-24%; B: 63-68%, the remainder being unavoidable impurity elements;
[0044] Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the coating is about 1:1:1:1;
[0045] The microstructure of the coating includes a crystalline phase and an amorphous phase.
[0046] The crystalline phase is a (TiHfMoNbZr)B2 solid solution of hexagonal aluminum diboride structure, with a grain size of 2 to 5 nm;
[0047] The amorphous phase is TiHfMoNbZrB alloy.
[0048] In the present invention, the molar ratio of Hf, Mo, Nb and Zr elements in the coating is about 1:1:1:1, which has the advantage of obtaining higher hardness, good comprehensive properties such as wear resistance, corrosion resistance and thermal stability.
[0049] In the present invention, four elements Hf, Mo, Nb and Zr are introduced into the TiB2 coating to adjust the microstructure of the coating. The advantage of using the above-mentioned atomic percentage range of Ti, Hf, Mo, Nb, Zr and B elements is that a part of 2-5% Hf, Mo, Nb and Zr elements will enter the TiB2 lattice to form (TiHfMoNbZr)B2 solid solution. Due to the different atomic radii of different metal atoms, lattice distortion will be caused; the other part will form an amorphous part together with a small amount of B, and the amorphous part will wrap the nanocrystal to form a nano-composite structure.
[0050] Furthermore, the fracture morphology of the coating is a dense structure (such as Figure 2), the thickness of the coating is 1.7 to 2.7 μm.
[0051] In the present invention, the fracture morphology of the coating shows a dense structure, and the coating quality is good.
[0052] Furthermore, the coating is prepared by co-deposition of a HfMoNbZr target by high-power pulsed magnetron sputtering and a TiB2 target by DC magnetron sputtering;
[0053] Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the HfMoNbZr target is 1:1:1:1.
[0054] Based on the same inventive concept, the present invention provides a method for preparing a nanocomposite structured ultrahard high entropy diboride coating, the preparation method comprising:
[0055] The substrate is placed in a vacuum coating device, and a HfMoNbZr target and a TiB2 target are used as target materials, wherein the HfMoNbZr target is connected to a high-power pulsed magnetron power supply, and the TiB2 target is connected to a direct current power supply;
[0056] In a vacuum environment, an inert gas is continuously introduced into the vacuum coating device, and a HfMoNbZr target and a TiB2 target are simultaneously turned on to deposit a nano-composite structure ultra-hard high-entropy diboride coating on the surface of the substrate;
[0057] Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the HfMoNbZr target is 1:1:1:1.
[0058] In the present invention, the HfMoNbZr target is sputtered by high-power pulse magnetron sputtering, and the TiB2 target is sputtered by DC magnetron sputtering. The advantage is that DC magnetron sputtering can provide a stable sputtering rate to ensure the basic thickness of the film, and high-power pulse magnetron sputtering can produce higher particle energy, which can increase the density of the coating, reduce defects, and improve the quality of the film.
[0059] Further, the magnetron sputtering power of the HfMoNbZr target is 80-220W, the pulse width is 20μs, the pulse frequency is 1000Hz, the magnetron sputtering power of the TiB2 target is 240-260W, the deposition temperature is 400-600℃, the deposition time is 180min, the substrate bias is a floating potential, and the rotation speed is 15±2r / min. In the present invention, the magnetron sputtering power of the HfMoNbZr target is 80-220W, and the magnetron sputtering power of the TiB2 target is 240-260W, which has the advantage of being able to form such a high-hardness coating with a nanocomposite structure.
[0060] In the present invention, the magnetron sputtering deposition temperature is 400-600° C., which has the advantage of improving the atomic diffusion migration capability and promoting the growth of crystal grains.
[0061] Furthermore, the distances between the HfMoNbZr target and the TiB2 target and the substrate are 8 to 11 cm, and the background vacuum of the vacuum coating equipment is less than 2×10 -3 Pa;
[0062] The flow rate of the inert gas is 38-42 sccm.
[0063] The following will describe in detail a nanocomposite structure ultra-hard high entropy diboride coating, a preparation method and an application thereof in combination with examples and experimental data.
[0064] Specifically, the present invention provides a method for preparing a nanocomposite structured ultra-hard high entropy diboride coating, comprising the following steps:
[0065] S1. Substrate pretreatment: After single-side polishing, the silicon wafer and 316L stainless steel substrate were rinsed with deionized water, and then cleaned with petroleum ether and anhydrous ethanol in an ultrasonic wave with a frequency of 30kHz for 15 to 20 minutes respectively. After cleaning, an air compressor was used to blow dry to remove surface oil and adhesive;
[0066] S2. Coating deposition: The cleaned substrate was fixed on the sample stage of the vacuum chamber. The HfMoNbZ target and TiB2 target were fixed on the cathode connected to the high-power pulsed magnetron power supply and the DC power supply respectively. The target-substrate distance was adjusted to 8-11 cm. The vacuum chamber door was closed and the vacuum chamber pressure was pumped down to 2×10 -3 Pa, heat the substrate to 400-600℃, maintain the temperature unchanged during deposition, introduce inert gas argon, the argon flow rate is 38-42sccm, the argon purity is ≥99.99%, adjust the air pressure in the vacuum chamber to 0.4-0.5Pa, turn on the high-power pulsed magnetron sputtering power supply of HfMoNbZr target with equimolar atomic ratio, the power is 80-220W, turn on the DC power supply of TiB2 target, the power is 240-260W, pre-sputter for 10min to remove impurities on the target surface, open the substrate baffle after 10min to deposit nano-composite structure ultra-hard high entropy diboride coating, the sample rotation speed is 15r / min, the deposition time is 180min, turn off the cathode power supply after the coating is completed, cool the vacuum chamber temperature to below 80℃, take out the sample for storage.
[0067] Since silicon wafers are of extremely high purity, they are often used for material characterization, which can ensure that the silicon substrate will not affect the characterization results. However, because they are too thin and brittle, they are not suitable for testing coating performance. The 316L substrate is used to test its wear resistance, but its composition is complex and not suitable for coating property characterization. Therefore, the nanocomposite structure ultra-hard high entropy diboride coating deposited on the silicon substrate is used for structural characterization and hardness testing, and the nanocomposite structure ultra-hard high entropy diboride coating deposited on the 316L stainless steel sheet is used for friction and wear testing.
[0068] The substrates of the following embodiments and comparative examples all include silicon sheets and 316L stainless steel sheets.
[0069] Example 1
[0070] This embodiment provides a method for preparing a nanocomposite structured ultra-hard high entropy diboride coating, and its specific process parameters are:
[0071] The background vacuum is 2×10 -3 Pa, the target and the substrate surface are fixed at 45°, the target-substrate distance is 11 cm, the substrate deposition temperature is 500°C, the argon flow rate is 40 sccm during coating deposition, the vacuum chamber pressure is controlled at 0.45 Pa during coating deposition, the HfMoNbZr target with an equimolar atomic ratio is sputtered using a high-power pulse power supply with a power of 100W, the TiB2 target is sputtered using a DC power supply with a power of 250W, the deposition time is 180min, and the sample is taken out after cooling to 80°C. The results of this embodiment show that the atomic content percentages of the elements in the coating are calculated to be B 67.72%, Ti 22.86%, Hf 2.22%, Mo 2.55%, Nb 2.41%, and Zr2.24% respectively; the phase structure is as follows Figure 1 As shown, the crystalline phase is a (TiHfMoNbZr)B2 solid solution with a hexagonal aluminum diboride (hcp) structure. The calculated grain size is 4 to 8 nm. The hardness is 34.031 GPa and the elastic modulus is 345.505 GPa ( Figure 3 ), the wear rate is 1.245×10 -15 m 3 ·N -1 ·m -1 .
[0072] In the present invention, nanoindentation measurement is performed using a nanoindentation system (TTX-NHT3, Anton Paar) to evaluate the hardness (H) and elastic modulus (E) of the coating, with a fixed load of 10 mN to ensure that the indentation depth does not exceed 10% of the coating thickness. Each sample is measured 12 times, and the average value and absolute error are calculated. A ball-disc tribometer (MFT-5000, Rtec) is used to test the wear resistance of the coating deposited on a 316L stainless steel sheet substrate to an Al2O3 ball with a diameter of 6 mm. The test adopts a linear reciprocating sliding mode, with a normal load of 2.5 N, a sliding speed of 8 mm / s, a wear track length of 4 mm, and a total sliding time of 50 minutes.
[0073] Example 2
[0074] The preparation method of this embodiment is basically the same as that of embodiment 1, the only difference being that the HfMoNbZr target power is 200W.
[0075] The results of this embodiment show that the atomic content percentages of the elements in the coating are B 63.54%, Ti21.44%, Hf 3.48%, Mo 4.02%, Nb 3.91%, and Zr 3.60% respectively; the crystalline phase is a (TiHfMoNbZr)B2 solid solution with a hexagonal aluminum diboride (hcp) structure; the grain size is 2-5 nm, the hardness is 41.821 GPa, the elastic modulus is 376.435 GPa, and the wear rate is 5.538×10 -16 m 3 ·N -1 ·m -1 .
[0076] Comparative Example 1
[0077] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that the HfMoNbZr target power is 0W.
[0078] The results of this embodiment show that the atomic content percentages of the elements in the coating are B 74.77% and Ti 25.23% respectively; the crystalline phase is a hexagonal aluminum diboride (hcp) structure; the grain size is 6-10 nm, the hardness is 26.629 GPa, the elastic modulus is 273.592 GPa, and the wear rate is 6.249×10 -15 m 3 ·N -1 ·m -1 .
[0079] Comparative Example 2
[0080] The preparation method of this embodiment is basically the same as that of embodiment 1, the only difference being that the HfMoNbZr target power is 300W.
[0081] The results of this embodiment show that the atomic content percentages of the elements in the coating are B 58.27%, Ti 19.67%, Hf 5.14%, Mo 5.31%, Nb 5.76%, and Zr 5.86%, respectively; the coating exhibits an amorphous structure, a hardness of 30.855 GPa, an elastic modulus of 336.313 GPa, and a wear rate of 1.577×10 -15 m 3 ·N -1 ·m -1 .
[0082] Figure 1 The XRD spectra of the high entropy diboride coatings prepared in the embodiments and comparative examples of the present invention show that the crystalline phase in the coatings is a hexagonal aluminum diboride structure. The diffraction peak angle of the embodiments is lower than that of comparative example 1, indicating that a (TiHfMoNbZr)B2 solid solution is formed in the coatings.
[0083] Figure 2 This is a cross-sectional morphology of the high entropy diboride coating prepared in Example 2 of the present invention. The coating has a dense structure and a thickness of about 2.1 μm.
[0084] Figure 3 The hardness and elastic modulus of the high entropy diboride coatings of the embodiments of the present invention and the comparative examples.
[0085] Figure 4 The high-resolution TEM image of the high-entropy diboride coating prepared in Example 2 of the present invention shows that the lattice constant increases, indicating that a (TiHfMoNbZr)B2 solid solution is formed. At the same time, it can be observed that the grain size is less than 10 nm, which is a nanocrystalline.
[0086] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0087] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0088] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A nanocomposite ultra-hard high entropy diboride coating, characterized in that: The chemical composition of the coating in atomic percentage is as follows: Hf: 2-5%; Mo: 2-5%; Nb: 2-5%; Zr: 2-5%; Ti: 20-24%; B: 63-68%, the remainder being unavoidable impurity elements; The microstructure of the coating includes a crystalline phase and an amorphous phase, wherein the crystalline phase is a (TiHfMoNbZr)B2 solid solution of a hexagonal aluminum diboride structure with a grain size of 2 to 5 nm; The amorphous phase is TiHfMoNbZrB alloy.
2. The nanocomposite ultrahard high entropy diboride coating according to claim 1, characterized in that: The hardness of the coating is 34-42 GPa, the elastic modulus is 340-378 GPa, and the wear rate is 5.5×10 -16 ~1.3×10 -15 m 3 ·N -1 ·m -1 .
3. A nanocomposite ultra-hard high entropy diboride coating according to claim 1 or 2, characterized in that: The fracture morphology of the coating shows a dense structure, and the thickness of the coating is 1.7 to 2.2 μm; The molar ratio of Hf, Mo, Nb and Zr elements in the coating is about 1:1:1:
1.
4. A nanocomposite ultra-hard high entropy diboride coating according to claim 1 or 2, characterized in that: The coating is prepared by co-deposition of a HfMoNbZr target by high-power pulsed magnetron sputtering and a TiB2 target by direct current magnetron sputtering; Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the HfMoNbZr target is 1:1:1:
1.
5. A method for preparing a nanocomposite ultrahard high entropy diboride coating according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The substrate is placed in a vacuum coating device, and a HfMoNbZr target and a TiB2 target are used as target materials, wherein the HfMoNbZr target is connected to a high-power pulsed magnetron power supply, and the TiB2 target is connected to a direct current power supply; In a vacuum environment, an inert gas is continuously introduced into the vacuum coating device, and power supplies of the HfMoNbZr target and the TiB2 target are simultaneously turned on to deposit a nano-composite structured ultra-hard high-entropy diboride coating on the surface of the substrate; Wherein, the molar ratio of Hf, Mo, Nb and Zr elements in the HfMoNbZr target is 1:1:1:
1.
6. The method for preparing a nanocomposite structured ultrahard high entropy diboride coating according to claim 5, characterized in that: The magnetron sputtering power of the HfMoNbZr target is 80-220W, the pulse width is 20μs, the pulse frequency is 1000Hz, the magnetron sputtering power of the TiB2 target is 240-260W, the deposition temperature is 400-600°C, the deposition time is 180min, the substrate bias is a floating potential, and the rotation speed is 15±2r / min.
7. The method for preparing a nanocomposite structured ultrahard high entropy diboride coating according to claim 5 or 6, characterized in that: The distances between the HfMoNbZr target and the TiB2 target and the substrate are both 8 to 11 cm, and the background vacuum of the vacuum coating equipment is less than 2×10 -3 Pa; The flow rate of the inert gas is 38-42 sccm.
8. The method for preparing a nanocomposite structured ultrahard high entropy diboride coating according to claim 5, characterized in that: The substrate is pre-surface treated to remove impurities on the substrate surface.
9. Use of the method for preparing a nanocomposite ultrahard high entropy diboride coating as claimed in any one of claims 5 to 8 in preparing a wear-resistant protective coating on the surface of a machined part.
10. Use of the method for preparing a nanocomposite ultrahard high entropy diboride coating according to any one of claims 5 to 8 in preparing tool coatings.
Citation Information
Patent Citations
A high-hardness corrosion-resistant coating, its preparation method and application
CN112323031B
A microcrystalline titanium diboride composite coating, its preparation method and application
CN113174571B